Options for Post-Election Conflict Resolution in Africa - Sixpence, Pedzisai; Chilunjika, Alouis; Sakarombe, Emmanuel (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
Elections in most emerging democracies are generally characterised by irregularities which in turn fuel violent and non-violent expressions of displeasure before, during and after the voting excise. This paper discusses options for post-election conflict resolution with focus on African experiences since 2000. The paper holds that political and nonpolitical, local and international actors, play a dire role in ensuring that election-related insecurities are at least pacified. The paper assessed the constitutional, political and diplomatic alternatives to post- election conflict resolution. The paper goes further to examine the challenges that faced by African states in their exertion to deal with post-election conflicts. The study provides recommendations to inform the successes of the he post-election conflict resolutions in Africa. This paper establishes that most African states have lucrative legal frameworks on conducting elections and dealing with post-election unfortunate eventualities, the most compromise comes from, however, lack of political will and respect for the municipal ad international regulations. Furthermore, the paper realises that the continent, in some cases, lacks capacity and effectiveness on policy implementation to enforce electoral outcome or court rulings.